Estudo e implementação de controle secundário em microrredes CC - Neves, Juliana Cunha (2023)
The growing increase of distributed generation (DG) coupled with the integration of information technologies into the electrical grid has revolutionized energy production and consumption dynamics. With in this context, microgrids are emerging as promising solutions for efficiently incorporating DG into the power grid. Despite the prevalence of alternating current in distribution systems, the growing demand for direct current (DC) loads and the presence of DC-based renewable energy sources are driving research and development in DC distribution systems. This study focuses on the utilization of DC microgrids with a primary emphasis on secondary control. An advanced microgrid seamlessly integrates DG, energy storage systems, and loads. However, this integration hinges on the formulation of effective control management strategies. DC microgrids are managed through a hierarchical control structure consisting of three levels: primary, secondary, and tertiary control. This work zeroes in on secondary control, which primarily serves two functions: 1) distribution of power/current, and 2) adjustment of DC voltage. A key challenge in implementing secondary control within DC microgrids is establishing an efficient communication network for information exchange among the converter units that compose the microgrid's topology. Hence, the objective of this research is to study, implement, and validate a communication methodology based on a distributed approach for an innovative power/current sharing technique among the converters within a DC microgrid. This communication framework enhances energy distribution between converters, consequently fostering stability and efficiency in microgrid operations. The evaluation of simulation results is performed using Matlab® software, employing the TrueTime toolbox within the Simulink environment. This approach facilitates the simulation of communication delays and failures, complemented by experimental outcomes using a prototype. When analyzing two communication topologies, the study unveils how the microgrid responds to load variations, disturbances, and communication failures. The analyses highlight the effectiveness of the secondary control in ensuring the stability of the DC bus by correcting deviations and in achieving efficient power distribution through the proposed approach.